2015
DOI: 10.1007/s00216-015-8854-4
|View full text |Cite
|
Sign up to set email alerts
|

Optimization strategies of in-tube extraction (ITEX) methods

Abstract: Microextraction techniques, especially dynamic techniques like in-tube extraction (ITEX), can require an extensive method optimization procedure. This work summarizes the experiences from several methods and gives recommendations for the setting of proper extraction conditions to minimize experimental effort. Therefore, the governing parameters of the extraction and injection stages are discussed. This includes the relative extraction efficiencies of 11 kinds of sorbent tubes, either commercially available or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…According to the high F values and low p values in Table 4, the number of strokes and the extraction temperature are the two parameters with the highest influence on the extraction yield [32,33]. In comparison, the extraction flow and desorption temperature are less decisive for the extraction yield.…”
Section: Extraction Parameter Optimization and Figures Of Meritmentioning
confidence: 96%
See 2 more Smart Citations
“…According to the high F values and low p values in Table 4, the number of strokes and the extraction temperature are the two parameters with the highest influence on the extraction yield [32,33]. In comparison, the extraction flow and desorption temperature are less decisive for the extraction yield.…”
Section: Extraction Parameter Optimization and Figures Of Meritmentioning
confidence: 96%
“…A combination of a high number of strokes (e.g., 80 strokes) with a slow extraction flow (e.g., 30 μL s −1 ) results in long sampling time [32], which is not favorable for prompt/practical applications. A decrease in the extraction yield is reported [32], when a high extraction flow (e.g., 100 μL s −1 ) is applied. Thus, a suitable extraction flow for initial trials would be 50 μL s −1 .…”
Section: Extraction Parameter Optimization and Figures Of Meritmentioning
confidence: 99%
See 1 more Smart Citation
“…Sample preparation remains one of the more time-consuming and error-prone aspects of analytical chemistry. To overcome drawbacks of conventional extraction techniques, alternative miniaturized methods have been proposed both as solid phase microextraction, as Solid Phase MicroExtraction (SPME) [7][8][9], MicroExctraction by Packed Sorbent (MEPS) [10], Stir Bar Sorptive Extraction (Twister, SBSE) [11], Solid Phase Dynamic Extraction (Magic Needle, SPDE) [12], In-Tube Extraction (ITEX) [13] and liquid phase microextraction like Single-Drop MicroExtraction (SDME) [14], Hollow Fiber LiquidPhase Microextraction (HF-LPME) [15,16], Dispersive Liquid-Liquid Microextraction (DLLME) [17], Solvent Bar MicroExtraction (SBME) [18]. On-sample derivatizations applied in miniaturized extraction systems and their simultaneous GC and liquid chromatography analysis has been described for the determination of analytes in aqueous matrices [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Laaks et al. published a guideline about optimization strategies for a successful analysis with ITEX . To save time and costs, it was shown that design of experiment can be used to determine optimal extraction parameters .…”
Section: Introductionmentioning
confidence: 99%